Sexual dimorphism in Hypselobarbus kurali (Pisces: Cyprinidae) - Sherly Williams, E.; Jean Jose, J.; Vijayalakshmi, P. V.; Razeena karim, L.; Vishnu Nair, M. S. (Journal of the Bombay Natural History Society (JBNHS), 2013)
No Abstract.